2023
DOI: 10.1186/s12891-023-06284-2
|View full text |Cite
|
Sign up to set email alerts
|

A real-world analysis of hybrid CDA and ACDF compared to multilevel ACDF

Abstract: Background Multilevel anterior cervical discectomy and fusion (mACDF) is the gold standard for multilevel spinal disease; although safe and effective, mACDF can limit regular spinal motion and contribute to adjacent segment disease (ASD). Hybrid surgery, composed of ACDF and cervical disc arthroplasty, has the potential to reduce ASD by retaining spinal mobility. This study examined the safety of hybrid surgery by utilizing administrative claims data to compare real-world rates of subsequent su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 16 publications
0
7
0
1
Order By: Relevance
“…Already, several biomechanical and clinical studies have demonstrated promising outcomes and suggest non-inferiority of HS compared with 2-level and 3-level ACDF. 23,[52][53][54] However, current literature is often limited by small sample size and relatively short follow-up. Future work may continue to expand on the impact of both location and number of ACDF and CDA, particularly for ≥ 3-level HS.…”
Section: Future Directionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Already, several biomechanical and clinical studies have demonstrated promising outcomes and suggest non-inferiority of HS compared with 2-level and 3-level ACDF. 23,[52][53][54] However, current literature is often limited by small sample size and relatively short follow-up. Future work may continue to expand on the impact of both location and number of ACDF and CDA, particularly for ≥ 3-level HS.…”
Section: Future Directionsmentioning
confidence: 99%
“…According to a recent retrospective analysis on the MarketScan Commercial database, Kim et al 23 reported on 558 HS between 2013 and 2020. They found that 2-level primary HS (60.9%) were the most common, followed by 3+-level primary (30.5%), and secondary HS (8.6%).…”
Section: Current Trends With Hybrid Constructsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cervical disc degenerative disease (CDDD) is a common spinal pathology that impacts many patients worldwide and has received extensive attention in the literature [1][2][3][4][5]. Estimates of the prevalence of CDDD in the literature range from 37% to 96%, depending on patient age [6].…”
Section: Introductionmentioning
confidence: 99%
“…Estimates of the prevalence of CDDD in the literature range from 37% to 96%, depending on patient age [6]. Numerous cervical surgical procedures exist for the treatment of CDDD, including anterior cervical discectomy and fusion (ACDF), cervical disc arthroplasty (CDA), and a combination of both of those procedures called hybrid cervical surgery (HCS) [1][2][3][4][5][7][8][9][10][11][12][13]. Patients can develop CDDD in a multi-level contiguous manner, in which adjacent levels of the cervical spine are affected, or in a non-contiguous manner, in which there is "skip-level" CDDD or level(s) of diseased cervical segments between level(s) of healthy cervical segments [1,[3][4][5]14,15].…”
Section: Introductionmentioning
confidence: 99%